2012
DOI: 10.1158/0008-5472.sabcs12-s1-11
|View full text |Cite
|
Sign up to set email alerts
|

Abstract S1-11: Meta-analysis Results from the Collaborative Trials in Neoadjuvant Breast Cancer (CTNeoBC)

Abstract: Background: Pathologic complete response (pCR) is a proposed surrogate endpoint for predicting long-term clinical benefit on endpoints such as disease-free survival (DFS), event-free survival (EFS), or overall survival (OS). A meta-analysis is needed to establish the magnitude of pCR improvement on a trial level that results in improved DFS, EFS, or OS. Methods: We identified 12 neoadjuvant randomized trials (N = 13,125) with pCR clearly defined and long-term follow-up available for EFS and OS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
4

Year Published

2013
2013
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 0 publications
1
47
1
4
Order By: Relevance
“…Within the ILC group, none of the survival endpoints were different between pCR and non-pCR patients after neoadjuvant chemotherapy. pCR is a surrogate endpoint for predicting long-term clinical benefit on endpoints such as disease-free or overall survival [9,30]. However, pCR seems especially important for tumours with more aggressive biological features.…”
Section: Discussionmentioning
confidence: 99%
“…Within the ILC group, none of the survival endpoints were different between pCR and non-pCR patients after neoadjuvant chemotherapy. pCR is a surrogate endpoint for predicting long-term clinical benefit on endpoints such as disease-free or overall survival [9,30]. However, pCR seems especially important for tumours with more aggressive biological features.…”
Section: Discussionmentioning
confidence: 99%
“…Triple-negative breast cancer (TNBC) and HER2-positive breast cancers were more likely to achieve path CR than hormone receptor (HR þ ) breast cancers, but when present, path CR was associated with significantly improved outcomes in all three subtypes. Another large meta-analysis based on pooling of individual patient data from 12 neoadjuvant randomized controlled trials reported that path CR after neoadjuvant chemotherapy was a strong predictor of improved DFS and OS (10). Moreover, the improved outcomes with path CR were in all the three breast cancer subtypes: HR þ (hazard ratio, 0.49; P < 0.001), HER2 þ (hazard ratio, 0.39; P < 0.001), and TNBC (hazard ratio, 0.24; P < 0.001), though for HR þ tumors, the association was stronger for grade 3 tumors (hazard ratio, 0.27; P < 0.001) than grade 1/2 tumors (hazard ratio, 0.63; P ¼ 0.07).…”
Section: Rationale For Drug Development In the Neoadjuvant Settingmentioning
confidence: 99%
“…Importantly, the I-SPY 1 trial (CALGB 150007/150012, ACRIN 6657) showed that pCR is a better predictor of recurrence-free survival by cancer subtype than for all patients as a whole, even among women with high-risk disease (10,11). These results were corroborated by the meta-analysis of randomized neoadjuvant trials (12).…”
Section: Why Use the Neoadjuvant Setting For Drug Developmentmentioning
confidence: 88%